The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1021/acs.jpcc.0c03637
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Conversion in Nonuniform Discharges: Disentangling Dissociation and Recombination Mechanisms

Abstract: Motivated by environmental applications such as synthetic fuel synthesis, plasma-driven conversion shows promise for efficient and scalable gas conversion of CO 2 to CO. Both discharge contraction and turbulent transport have a significant impact on the plasma processing conditions, but are, nevertheless, poorly understood. This work combines experiments and modeling to investigate how these aspects influence the CO production and destruction mechanisms in the vortex-stabilized CO 2 microwave plasma reactor. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(103 citation statements)
references
References 41 publications
(106 reference statements)
3
91
0
Order By: Relevance
“…In practice, VT relaxation appears quite important in both MW plasmas (at (sub)atmospheric pressure) and GA plasmas, explaining their high gas temperature (3000 K or higher). For this reason, the CO 2 conversion proceeds mainly by thermal reactions in MW and GA plasmas at practical operating conditions, as demonstrated by several models [271,294,[298][299][300][301][302]. However, Pietanza et al recently studied in detail the kinetics vs thermodynamics effects on CO 2 dissociation in high-temperature MW plasmas, with a self-consistent model of the vibrational kinetics of CO 2 , CO and O 2 , and the electron Boltzmann equation, and they concluded that the assumption of thermodynamic equilibrium in MW CO 2 high temperature plasmas has to be considered with caution, as there are still non-equilibrium effects at play, even at temperatures of 3500-5500 K [271].…”
Section: Insights Obtained From 0d Kinetic Models Of Co 2 Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, VT relaxation appears quite important in both MW plasmas (at (sub)atmospheric pressure) and GA plasmas, explaining their high gas temperature (3000 K or higher). For this reason, the CO 2 conversion proceeds mainly by thermal reactions in MW and GA plasmas at practical operating conditions, as demonstrated by several models [271,294,[298][299][300][301][302]. However, Pietanza et al recently studied in detail the kinetics vs thermodynamics effects on CO 2 dissociation in high-temperature MW plasmas, with a self-consistent model of the vibrational kinetics of CO 2 , CO and O 2 , and the electron Boltzmann equation, and they concluded that the assumption of thermodynamic equilibrium in MW CO 2 high temperature plasmas has to be considered with caution, as there are still non-equilibrium effects at play, even at temperatures of 3500-5500 K [271].…”
Section: Insights Obtained From 0d Kinetic Models Of Co 2 Plasmasmentioning
confidence: 99%
“…The authors showed the calculated 2D profiles of electron temperature, electron density, gas temperature and vibrational temperature at different moments in time, providing useful insights in the arc behavior of the CO 2 GA plasma. [300]. In this model, the power deposition was assumed to lead to direct gas heating, so vibrational kinetics was neglected, which was justified by the fast thermalization and the fact that thermal conversion dominates over vibrationinduced dissociation at the high temperatures under study.…”
Section: D/3d Fluid Models Necessity For Spatial Distribution Descriptionmentioning
confidence: 99%
“…The contraction of a vortex-stabilised CO 2 MW plasma has been characterised in Wolf et al (2019) in relation to its dielectric properties. Then, in Wolf et al (2020b), two distinct contracted discharge modes have been identified and described at pressures above 85 mbar: a low-confinement L-mode at lower pressures and at temperatures between 3000 and 5000 K and a high-confinement Hmode at higher pressures and at temperatures above 5500 K. The works in Viegas et al (2020) and Wolf et al (2020a) have investigated the contracted modes numerically. The distinct changes in spatial profiles of n e and P abs with discharge modes have been shown to be important to obtain accurate descriptions of the reactivity within the plasma, that determines the spatial structure of the plasma itself (Viegas et al 2020), as well as of the follow-up reactions of plasma products in its periphery, that influence the reactor performance (Wolf et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that this limit can be increased significantly by controlling the quenching trajectory of the atomic oxygen generated in reaction R1. Association of O with CO 2 yields an additional CO for each O 2 which, would increase the efficiency limit to 70% 6,8 by valorizing the enthalpy of formation of nascent O atoms:…”
mentioning
confidence: 99%